2017
DOI: 10.1103/physrevb.96.035407
|View full text |Cite
|
Sign up to set email alerts
|

Tunable quasiparticle band gap in few-layer GaSe/graphene van der Waals heterostructures

Abstract: demonstrate the tunability of the quasiparticle energy gap of few layered gallium selenide (GaSe) directly grown on a bilayer graphene substrate by molecular beam epitaxy (MBE). Our results show that the band gap is about 3.50 ± 0.05 eV for single-tetralayer (1TL), 3.00 ± 0.05 eV for bi-tetralayer (2TL) and 2.30 ± 0.05 eV for tritetralayer (3TL). This band gap evolution of GaSe, in particularly the shift of the valence band with respect to the Fermi level, was confirmed by angle-resolved photoemission spectros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 49 publications
8
104
1
Order By: Relevance
“…We have further investigated the electronic properties of nominal bilayer GaSe films by photoemission electron momentum microscopy (k-PEEM) and confirmed the Mexican-hat shaped dispersion in the upper valence band. 20 These results demonstrate that MBEgrown GaSe films can be an ideal platform for investigation of new physics in atomically thin monochalcogenides.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…We have further investigated the electronic properties of nominal bilayer GaSe films by photoemission electron momentum microscopy (k-PEEM) and confirmed the Mexican-hat shaped dispersion in the upper valence band. 20 These results demonstrate that MBEgrown GaSe films can be an ideal platform for investigation of new physics in atomically thin monochalcogenides.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, we speculate that our MBE-grown film contains a lower concentration of vacancies or impurities associated with p-type doping than the bulk counterparts or n-type GaSe grown on epitaxial graphene. 20 In order to have a finer look at the upper valence band features of bilayer GaSe, we performed k-PEEM measurements at a higher analyzer energy resolution of~100 meV and focused on the topmost upper valence band (Γ 1 + ) near the Γ point. 12 The acquired band structures and the second-derivative band structures are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, previous ARPES experiments on monolayer metal monochalcogenides have used materials grown by molecular beam epitaxy. [18][19][20][21] Most transport and optical investigations instead use mechanically exfoliated flakes which, though higher-quality, are typically only a few µm across. We have recently demonstrated that sub-micrometer spatially resolved ARPES (µARPES) enables high resolution measurements from mechanically exfoliated flakes.…”
mentioning
confidence: 99%
“…GaSe is a layered metal monochalcogenide crystal with two planes of Ga atoms sandwiched by two planes of Se atoms in each primitive layer. Unlike the well‐studied layered transition metal dichalcogenides, the thinning of GaSe from bulk to few‐layers will drive a direct‐to‐indirect bandgap transition, and the bandgap could be tuned reliably by controlling the layer numbers and doping levels in GaSe's van der Waals heterostructures . As a well‐known nonlinear crystal over the spectral range from visible to terahertz, GaSe's monolayer has a second‐order nonlinear coefficient about one order of magnitude larger than that of monolayer MoS 2 .…”
Section: Introductionmentioning
confidence: 99%